The Pattern of Clinical Characteristics of Tubercular Meningitis (TBM) Patients in Pediatric Unit of Magura Medical College Hospital (Medicine Today, 2025)
Introduction with Objectives: In this study our main goal is to evaluate the clinical characteristics of tubercular meningitis (TBM) patients in pediatric unit of Magura Medical College Hospital. Materials and Methods: An experimental design was conducted in pediatric unit of Magura Medical College Hospital from January 2021 to June 2024. 26 cases of tubercular meningitis confirmed by CSF study or confirmed by conservative treatment with antiTB were included for study. Results: In the present study, among the study subjects 55% had anemia, 96% had neck rigidity, 8% had cranial nerve palsy, 45% had kernig's sign and 22 % had long tract sign. Among them most prevalent symptom was fever (92%). Among others, headache (67%), altered consciousness (46%), vomiting (40%) and neck stiffness (25%) were notable. Conclusion: Finally we conclude that tubercular meningitis is a very serious form of tuberculosis that can occur in different forms and can cause mortality and morbidity in endemic developing countries and also in developed countries due to emergences of immune compromised conditions. Further study is needed for better outcome.Medicine Today 2025, Vol.37 (1): 99-101